Rapid Growth in Transition Economies : Growth-Accounting Approach - Iradian, Garbis (IMF Working Papers; Working Paper ;, 2007)
This paper uses the growth-accounting approach to determine the sources of growth in transition economies. The central conclusion is that the estimated total factor productivity (TFP) growth for the former Soviet Union republics were significantly higher than other fast growing economies. A key question for prospective growth is whether the TFP gains achieved thus far have already eliminated most of the inefficiencies of central planning-and will therefore soon fade away. Underutilized labor combined with the recent trend of faster capital accumulation may play a more important role in the medium-term growth.